Linear acceleration at head impact in collegiate divers: a pilot study - Wood, T. A.; Tablerion, J. M.; Ballard, R. A.; Zimmerman, J.; Sosnoff, J. J. (International Journal of Athletic Therapy & Training, 2021)
There is minimal biomechanical research examining head impacts in noncollision sport, such as diving. This pilot study quantified the number of head impacts and magnitude of linear head acceleration in collegiate divers. Three participants wore instrumented swim caps for 10 practice sessions. A total of 1,271 dives were recorded and analyzed. Acceleration at impact ranged from 24.1g to 33.3g for 1-m dives and from 31.6g to 38.4g for 3-m dives. Simple main effects were observed for dive type (p > .001) and dive distance (p > .001). The current data suggest diving athletes experience considerable head acceleration, yet more research is needed to understand the potential implications.